Development of HPLC Method for the Estimation of Valacylovir in Tablet Dosage Form - SRINU BABU, G.; SARAT BABU, I.; KIRAN KUMAR, N.; YUGANDHAR, N.M.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive and precise high performance liquid chromatographic method has been developed for the estimation of valacyclovir in bulk and tablet dosage form. In this method, RP-C18 column with mobile phase consisting of acetonitrile and buffer in the ratio of 85:15 (mobile phase A) and only methanol (mobile phase B) gradient mode was used. The detection wavelength is 250 nm and the flow rate is 0.6 mL/min. In the range of 0.2-8.0 mg/mL, the linearity of valacyclovir shows a correlation coefficient of 0.9999. The proposed method was validated by determining sensitivity, accuracy, precision and system suitability parameters.